Laparoscopic vs. robotic sacrocolpopexy: influence of age, BMI, and parity on perioperative outcomes - Strauss, Mila; Kennes, Lieven N.; Dombrowski, Janina; Stickeler, Elmar; Gräf, Charlotte; Lube, Katharina; Hillmeyer, Alessia; Najjari, Laila (Frontiers in Surgery, 2025)
BackgroundLaparoscopic and robotic-assisted sacrocolpopexy are established techniques for pelvic organ prolapse (POP) repair, but their performance in patients with higher age, BMI, and parity remains underexplored.MethodsIn this retrospective single-center study, we analyzed 162 women undergoing minimally invasive sacrocolpopexy between 2010 and 2023: n = 104 via laparoscopic sacrocolpopexy (LSC) and n = 58 via robotic-assisted sacrocolpopexy (RASC). Patients were included if they had symptomatic or asymptomatic POP stage II or higher. Primary outcomes were surgical duration and length of postoperative hospital stay; secondary outcomes included intra- and postoperative complications. Regression analyses were used to assess the influence of age, BMI, and number of births.ResultsMean patient age was 64 ± 11.2 years. Surgical duration increased significantly with BMI (+2.82 min/unit, 95% CI: 0.50, 5.14, p = 0.0177) and parity (+9.8 min/birth, CI: 0.56, 19.14, p = 0.0379) in the LSC group, but not significantly in RASC (Surgical duration: (+2.00 min/unit, 95% CI: −0.53, 4.63, p = 0.1167; parity: + 8.7 min/birth, 95% CI: 0.50, 5.14, p = 0.0698). Postoperative stay was significantly prolonged with higher age (95% CI = 0.006, 0.057, p = 0.0152), BMI (95% CI = 0.019, 0.154, p = 0.0130), and number of vaginal births (95% CI = 0.008, 0.59, p = 0.01) in LSC, while these associations were attenuated in RASC (age: 95% CI: −0.0213, 0.0249, p = 0.876; BMI: −95% CI: −0.038, 0.060, p = 0.667; vaginal birth: 95% CI = 0.10, 0.44, p = 0.003). Overall complication rates exhibited no measurable difference between the groups (LSC 18%, RASC 19%). Complications were more frequent with fixation at the vaginal vault than the cervix.ConclusionRobotic-assisted sacrocolpopexy appears to offer greater procedural consistency in patients with advanced age, obesity, and higher parity. These findings support the selective use of robotic assistance in anatomically or clinically complex cases and add to the limited evidence guiding personalized surgical planning in POP repair.